ANSWER
Step-by-step explanation
To solve this equation, first, square both sides of the equation,
![(\sqrt[]{25-3x})^2=(x-9)^2](https://img.qammunity.org/2023/formulas/mathematics/college/1hcgjp9sk1a3u2k9c5d7e6xs5zkqukqm2k.png)
Simplify the square root with the exponent and expand the binomial squared on the right side of the equation,
![25-3x=x^2-18x+81](https://img.qammunity.org/2023/formulas/mathematics/college/qjqw4t5itbht1hyvmu8k935k8mkim09tsi.png)
Then, subtract 25 from both sides and add 3x to both sides,
![\begin{gathered} 25-25-3x+3x=x^2-18x+3x+81-25 \\ \\ 0=x^2-15x+56 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/x56me687cfcabj10jfgc113fc81yvcn9s2.png)
This is a quadratic equation that we can solve using the quadratic formula,
![\begin{gathered} if\text{ }ax^2+bc+c=0 \\ then\text{ }x=\frac{-b\pm\sqrt[]{b^2-4ac}}{2a} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/1eod0th1uvpaw0vtc6tkx2t3z2qxfz3n2k.png)
In this case, the coefficients are a = 1, b = -15 and c = 56,
![undefined]()